Discrete-event system abstractions for on-line logical and real-time hierarchical control - Ngo, Quang Ha (2016)
This thesis addresses two abstraction problems for two-level hierarchical control of discrete-event systems (DES's). DES's are dynamic systems driven by asynchronous events evolving through discrete states. The first problem is state abstractions of controllable outputs for realizing hierarchical control of logical DES's as on-line command and control. On-line command and control may be the runtime operational mode for some engineering applications, or required when subjecting a control solution to validation tests by simulation and observation. The problem is addressed by formulating, for a reference output set, a new abstraction concept for output control feasibility of a DES modeled by a Moore automaton, and a system decomposition of a Moore automaton with a natural output control structure into a controllable subsystem and an uncontrollable subsystem. These results are then used to implement the new command and control design, which is shown to offer the intrinsic merit of furnishing causal clarity of command over control during on-line operation, along with off-line complexity reduction and fast on-line computation, and can therefore more efficiently and effectively support the intended application use. The second problem addressed is the abstraction of system for hierarchical consistency of timed DES's (TDES's) with output-time fidelity. Characterization of system output-time fidelity is essential to furnish a sound real-time high-level specification design foundation for hierarchical control. The problem is addressed by unearthing the fundamental properties of preemptability and fidelity of system atomic time modeled by a special tick event, and formulating the necessary real-time concepts for hierarchical consistency of TDES's - without and with output-time fidelity guarantee. In terms of the concepts developed, results for the structural existence and synthesis of the sufficiency structure for hierarchical consistency with no output-time fidelity guarantee are developed. It is then shown that a class of Moore TDES's exists whose structure can be refined to achieve hierarchical consistency with output-time fidelity, and is a linear subclass of a mildly restrictive class of TDES's whose structure can be refined to achieve hierarchical consistency with no output-time fidelity guarantee.